Prehospital Intubation in Patients with Isolated Severe Traumatic Brain Injury: A 4-Year Observational Study - Mazin Tuma; Ayman El-Menyar; Husham Abdelrahman; Hassan Al-Thani; Ahmad Zarour; Ashok Parchani; Sherwan Khoshnaw; Ruben Peralta; Rifat Latifi (Critical Care Research and Practice)
Objectives. To study the effect of prehospital intubation (PHI) on survival of patients with isolated severe traumatic brain injury (ISTBI). Method. Retrospective analyses of all intubated patients with ISTBI between 2008 and 2011 were studied. Comparison was made between those who were intubated in the PHI versus in the trauma resuscitation unit (TRU). Results. Among 1665 TBI patients, 160 met the inclusion criteria (105 underwent PHI, and 55 patients were intubated in TRU). PHI group was younger in age and had lower median scene motor GCS (P=0.001). Ventilator days and hospital length of stay (P=0.01 and 0.006, resp.) were higher in TRUI group. Mean ISS, length of stay, initial blood pressure, pneumonia, and ARDS were comparable among the two groups. Mortality rate was higher in the PHI group (54% versus 31%, P=0.005). On multivariate regression analysis, scene motor GCS (OR 0.55; 95% CI 0.41–0.73) was an independent predictor for mortality. Conclusion. PHI did not offer survival benefit in our group of patients with ISTBI based on the head AIS and the scene motor GCS. However, more studies are warranted to prove this finding and identify patients who may benefit from this intervention.